Pengaruh Bauran Pemasaran (Marketing Mix) terhadap Keputusan Menggunakan Jasa Rawat Jalan di Rumah Sakit Bina Sehat Jember - Ulfah, Maria; Rachmi, Asih Tri; Yuniarinto, Agung (Universitas Brawijaya, Indonesia, 2013)
This study aims to figure out the general description of marketing mix including: product, price, place, promotion, people, process and physical evidence, that is related to the decision to utilize outpatient services at Bina Sehat Hospital Jember; besides, this research also aims to figure out both simultaneous and partial influences of marketing mix on the decision to utilize outpatient service of Bina Sehat hospital Jember. The study conducts analytical survey (non experimental) with a cross-sectional approach on 80 patients of polyclinic Bina Sehat hospital Jember. The sample is taken using purposive sampling technique. The Independent variables are product, price, place, promotion, people, process and physical evidence; whereas, the dependent variable is decision to utilize outpatient service at Bina Sehat hospital Jember. The variables are measured by questionnaires instrument. The study is conducted at outpatient polyclinic Bina Sehat hospital Jember. Formerly, before the questionnaire is used, the researcher tests its validity and reliability. The instrument's validity utilizes product moment correlation; while the reliability test uses Cronbach alpha method. The data are analyzed by utilizing multiple linear regression analysis.The study reveals that marketing mix simultaneously and significantly affects the decision of taking outpatient services at Bina Sehat hospital Jember. The Ris 0.809; it implies that the ability of the independent variables consisting of Products (X1), Price (X2), Place (X3), Promotion (X4), People (X5), Process (X6) and Physical Evidence (X7), is able to explains the variability of dependent variable, which is the decision to utilize outpatient service (Y), as much as 80.9%. The rest, or 19.1%, is explained by other independent variables which are not observed in this study. Product,place, promotion, people and physical evidence affect the decision to utilize services of Bina Sehat hospital; meanwhile, price and process variables do not significantly affect the decision to utilize outpatient services. The dominant dependent variable which affects the decision to utilize outpatient services (Y) is product (X1) as it counts for 29.94%; in addition, the other influence comes from physical evidence (X7) which counts for 18.77%, place (X3) which counts for 14.76 %, promotions (X4) which counts for 12.10%, People (X5) which counts for 9.72%, Process (X6) which counts for 3.94% ,and Price (X2) which counts for 0.55%